Maritime Mobilities in Anglophone Literature and Culture - Ganser, Alexandra; Lavery, Charne (Maritime Literature and Culture, 2023)
This open access edited collection explores various aspects of how oceanic im/ mobilities have been framed and articulated in the literary and cultural imagination. It covers the entanglements of maritime mobility and immobility as they are articulated and problematized in selected literature and cultural forms from the early modern period to the present. In particular, it brings cultural mobility studies into conversation with the maritime and oceanic humanities. The contributors examine the interface between the traditional Eurocentric imagination of the sea as romantic and metaphorical, and the materiality of the sea as a deathbed for racialized and illegalized humans as well as non-human populations